Parallel Implicit Solution of Full Navier-Stokes Equations - Vildan Üstoglu Ünal; Ü, Gülçat (Springer Berlin Heidelberg, 2003)
Parallel implicit solution of the incompressible Navier-Stokes equations based on two fractional steps in time and Finite Element discretization in space is presented. The accuracy of the scheme is second order in both time and space domains. Large time step sizes, with CFL numbers much larger than unity, are taken. The Domain Decomposition Technique is implemented for parallel solution of the problem with matching and non-overlapping sub domains. The segragate solution to tempereature field is obtained for the flow case where the forced convection is one order of magnitude higher than the free convection.